The Consideration of Response Modification Factor of L-Shaped Structures by Using Adaptive Pushover Analysis Method and Comparison with Traditional Pushover Method - Azin Akbari; Erfan Ordookhani; Mohammad Reza Pasaeian (Civil Engineering Journal, 2018)
In the most of regulations, reduction factor of seismic force depends only on the kind of lateral loading system, but research has shown that this factor is a function of many factors such as period and modal characteristics of the structure, the height and especially form of plan in the building. Due to the complexity of nonlinear dynamic analysis method, today, nonlinear static analysis method called pushover, as a practical appropriate tool has developed in field of earthquake engineering based on function frequently. But traditional pushover analysis method have defects that can be noted Including the stability of lateral load pattern form, did not consider the impact of higher modes or impact of more efficient modes and lack of consideration of the stiffness matrix of member or the entire of structure changes in step of analysis. In recent years a number of researchers have proposed using adaptive load pattern, in this methods, lateral load pattern have changed and adapting in during analysis based on momentary stiffness matrix of structures. In this paper we investigate the response modification factor in L-shaped geometric asymmetry by using SAP software, Pushover analysis used in this study is divided into two categories pushover with constant load pattern (traditional method) and pushover with the adaptive load pattern (adaptive). So, it is studied building with L-shaped asymmetrical plan, with moment frame double structural system - bracing and number of floors 5, 10, 15 and 20, with four different bracing plan types at considering frames, and the end were compared obtained response modification factor from the two methods for these buildings.